Cerebral toxoplasmosis in a middle-aged man as first presentation of primary immunodeficiency due to a hypomorphic mutation in the CD40 ligand gene. Issue 11 (27th October 2008) - Yong, P F K; Post, F A; Gilmour, K C; Grosse-Kreul, D; King, A; Easterbrook, P; Ibrahim, M A A
Abstract : Cerebral toxoplasmosis can occur outside the setting of advanced HIV immunodeficiency or drug-induced immunosuppression. A case of cerebral toxoplasmosis is reported in a previously healthy 41-year-old man who was found to have a genetic defect in CD40 ligand, resulting in the X linked hyper-IgM syndrome despite normal surface protein expression on flow cytometry. This highlights the fact that primary immunodeficiencies can first present late in life with a relatively mild phenotype and should be considered in the differential diagnosis of opportunistic infections in non-HIV infected patients; in addition, normal protein expression does not necessarily rule out hypomorphic mutations.